Development of microsatellite markers for Carallia brachiata (Rhizophoraceae)(1) - Qiang, Yinmeng (Appl Plant Sci, 2015)
PREMISE OF THE STUDY: Microsatellite markers were developed for Carallia brachiata to assess the genetic diversity and structure of this terrestrial species of the Rhizophoraceae. METHODS AND RESULTS: Based on transcriptome data for C. brachiata, 40 primer pairs were initially designed and tested, of which 18 were successfully amplified and 11 were polymorphic. For these microsatellites, one to three alleles per locus were identified. The observed and expected heterozygosities ranged from 0 to 0.727 and 0 to 0.520, respectively. In addition, all primers were successfully amplified in two congeners: C. pectinifolia and C. garciniifolia. CONCLUSIONS: The microsatellite markers described here will be useful in population genetic studies of C. brachiata and related species, suggesting that developing microsatellite markers from next-generation sequencing data can be efficient for genetic studies across this genus.